Editorial: Multiple Perspectives on Interiority - Atmodiwirjo, Paramita (Interiority, 2018)
This journal challenges the emergence of various perspectives in defining and developing further design research agenda and promotes multidisciplinary dialogue in exploring the idea of interiority. It also hopefully becomes the trigger for extending the practice of design - architecture, interior design, spatial design and other relevant design fields - to address more appropriately the social, cultural and behavioural aspects of the space inhabitation.